An effective method for preventing chain from snatching - Prakash, M.; Nandhini, K.; Narmatha, K.; Swetha, SV.; Srikanth, J. (International Journal of Engineering and Technology, 2017)
Chain snatching is a serious threat scaring the public and a challenging issue for the police department to trace the offenders and recover the gold. To resolve this issue, the city police installed CCTV cameras and organized awareness programmes in crowdy places. These initiatives reduced the crime to certain extent. However, things remain the same and chain snatching has considerably increased. As offenders usually target the women in the society, it is very difficult to recover emotionally the affected women by such incidents. In this paper, it is proposed to design a small electronic gadget to track continuously when the chain is snatched. This gadget uses power from the human body, wearable sensors to track the location, and wireless transmission technology with smart phones over long distances. This innovative design will reduce the anti-social activities in public places. It can also be used as a life saver during accidents in remote areas.